Description de la compréhension du CECR Niveau A1 pour les enseignants de français dans les écoles secondaires à Bandar Lampung - Diana Rosita; Nani Kusrini (Universitas Hasanuddin, 2021)
The purpose of this study is to describe the competencies contained in the CECR A1 French language teaching standards in secondary schools in Bandar Lampung, and the 2013 curriculum objectives applied in schools. The method used to answer the problems is the descriptive-analytical method. According to the results of the questionnaires and the interviews conducted in five high schools, most French teachers already had already the knowledge of the CEFL, but limited to its relation with the DELF, not as a guide for the teaching standardized French at the international level. It also shows that teaching does not always follow the lesson plans. Because of this difference, teachers need training related to CEFL learning practices. It was therefore decided to provide training for teachers, leading to a convention of agreement governing the training of teachers in French learning practices according to level A1 of the CECR.